Colorimetric Detection of Bovine Serum Albumin (Bsa Protein) by Interaction and Modification of Silver Nanoparticles - Paez-Collio, M; Paez-Collio, M; Azocar-Guzman, M; Azocar-Guzman, M; Walter, M; Walter, M (American Chemical Society, 2025)
The detection of serum albumin is of great relevance because its presence in urine above normal levels is implicated in different pathologies, such as Diabetes Mellitus and Preeclampsia. The main objective of this work was to develop a protocol to sense serum albumin using the well-known unusual optical phenomenon that nanoparticles present, which is called surface plasmon resonance (SPR), as well as the influence of proteins on the size and morphology of nanoparticles, and consequently, on the SPR. The interaction of these nanoparticles with proteins forms biocoronates, which modify the optical and morphological properties of nanostructures. This behavior could be important for the construction of colorimetric sensors for medical or environmental applications. Considering the above, in the present study, we propose to sense Serum Albumin in the presence of silver nanoparticles (AgNps) for its determination and quantification under various physiological conditions that simulate the environment of human urine. The analysis of the growth of small AgNps (seeds) in the presence of the protein generated colorimetric changes, which were a function of pH, urea content, and chloride concentration. The presence of Serum Albumin also produced variations in the morphology and size of nanoparticles. With this methodology, the quantification of BSA was determined in a concentration range between 0.28 and 0.75 g/L and in less than 5 min of reaction. © 2025 The Authors. Published by American Chemical Society.